Green Accounting and Sales Growth: A Strategy Toward Sustainable Financial Performance in Energy Companies in Indonesia: Array - Puspita Handayani; Ayumi Rahma; Adhitya Putri Pratiwi; Listiya Ike Purnomo (JASS (Journal of Accounting for Sustainable Society), 2025)
This study aims to analyze the effect of green accounting and sales growth on the financial performance of energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Financial performance is proxied by Return on Assets (ROA), while green accounting is measured using an environmental CSR cost index relative to net income after tax. Sales growth is calculated based on the percentage change in annual sales. This research employs a quantitative approach using secondary data, and the analytical technique applied is multiple linear regression through SPSS software version 23. The results show that green accounting has a negative effect on financial performance, whereas sales growth has a positive effect. Simultaneously, both variables significantly influence financial performance. These findings imply that although environmental initiatives are important for social legitimacy, their implementation needs to be more efficient and value-oriented. Meanwhile, sales growth proves to be a key factor in driving the profitability of energy companies in Indonesia